PLAYING ORIGAMI DAN ITS IMPACT ON FINE MOTOR SKILLS DEVELOPMENT OF CHILDREN AGED 4-5 - Aghnia Nur Anisa; Ulwan Syafrudin; Rizky Drupadi (Journal of Early Childhood Education (JECE), 2021)
This study aims to determine the effect of origami activities on the fine motor skills of children aged 4-5 years. This research is using an experimental design. This research was conducted in the CABI Tanggamus learning group, which was conducted on fifteen children using a one-group pre-test post-test design. Data collection techniques used in this study are observation and documentation. In this study, the pre-test results of children's motor skills were included in the Starting to Develop (MB) category, meaning the child obtained an average score of 26 from a maximum score of 72. After the treatment, fine motor skills were included in Developing as Expected (BSH). The results obtained after treatment showed a score of 58 from a maximum score of 72. The results of this study can be concluded that origami play activities can affect the fine motor skills of early childhood, which means that origami games provide changes in children's fine motor development. Based on the results of the study, the researcher recommends origami games to improve fine motor skills.